The Missing Concordat in the Czech Republic = Le concordat manquant en République tchèque = Il concordato mancante nella Repubblica Ceca - Přibyl, Stanislav (Philosophy & canon law, 2022)
The present article discusses certain aspects of the Treaty between the Czech Republic and the Holy See. The text of the treaty was signed at the level of the government, however, it has not been ratified so far. Some provisions of the treaty are rather superfluous or lack sufficient normative basis. Nevertheless, as the example of Article 9 of the treaty on the recognition of civil effects of church marriages shows that the approval of the treaty by the Parliament of the Czech Republic would have been very beneficial. In fact, in the process of preparation for a new civil code an attempt was made to repeal church marriages recognized by the state. Such a project would have been made impossible by the concordat because church marriage would have been supported by an obligation of the state under international law. Fortunately, the civil code kept church marriages, and confessional law in the Czech Republic has to develop without a valid concordat.